Behavioural Factors Influencing the Adoption of Manuring in Immature Rubber (Hevea brasiliensis) Cultivations of Smallholder Rubber Farmers in Monaragala District - Gunarathne, P. K. K. S.; Siriwardana, K.D.K.L.; Premarathne, K.H.D.M. (University of Jaffna, 2024)
This study was carried out to examine behavioural factors that influence smallholders in the adoption of manuring in immature rubber (Hevea brasiliensis) cultivations (MIRC) introduced to Monaragala by the Rubber Research Institute of Sri Lanka. The data were collected employing a self-administered survey from 798 rubber smallholders in Moneragala in 2023 using stratified random sampling. The conceptual model was developed based on the decomposed theory of planned behaviour. The responses of rubber smallholders for validated items were captured on a five-point Likert scale. The conceptualized model was empirically tested using partial least square structural equation modelling by a bootstrapping procedure using the SMART-PLS 3.2 software. The composite nine-predictor conceptual framework and structural model were validly and reliably capable of explaining 78% of the variance in the adoption by rubber smallholders. This study identified seven behavioural factors; attitude, perceived usefulness, perceived ease of use, behavioural intention, facilitation condition, subjective norms, and perceived behavioural condition that act as drivers for the adoption of MIRC. The most significant influential factor is the facilitation condition and policymakers should pay more attention to improving it, which could be helped by improvement in the advisory services. In order to enhance the adoption of MIRC, a favourable environment contributing to these psychological factors should be improved among the rubber smallholders in Monaragala.
Keywords: Advisory service; Decomposed theory of planned behaviour; Manure adoption; Rubber farmers